How should international judicial bodies constituted under UNCLOS determine if they have jurisdiction over disputes involving territorial sovereignty? - Liu, Chenhong (Frontiers in Marine Science, 2022)
For the court or tribunal constituted under the United Nations Convention on the Law of the Sea (UNCLOS), there are mainly three conditions which limit its jurisdiction to the disputes concerning the interpretation and application of UNCLOS which involves sovereignty issues: firstly, if the nature of the dispute is deemed as the sovereignty dispute; secondly, if the prerequisite to adjudicate the dispute is the settlement of the sovereignty dispute; and thirdly, if the adjudication/arbitration of the dispute will advance or detract a state’s sovereignty claim. However, not all of the disputes involving territorial sovereignty are excluded from the jurisdiction of the court or tribunal. Provided that the court judgment or arbitral award will not affect the settlement of the sovereignty dispute between the disputed states or the claim to sovereignty of any state, it may, to a certain extent, has jurisdiction over a dispute of the interpretation and application of UNCLOS with territorial sovereignty disputes ancillary to it.